Back Cover: Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation (Angew. Chem. Int. Ed. 13/2023). Issue 13 (6th March 2023) - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan
Abstract : One‐electron oxidation converts the ferrocene‐substituted borane into a Lewis superacid, as reported by Frank Breher, Jan Paradies, and co‐workers in their Communication (e202216959) . The Lewis superacid activates almost inert carbon–fluorine and sulfur–fluorine bonds for reductions, alkylations, and arylations to form new chemical bonds.